Properties of composite nanomaterials for gas sensor applications - Diantantu, Aime Diakanwa (University of the Witwatersrand, Johannesburg, 2023)
Sensors are- important devices nowadays that have been instrumental towards the development of the Internet of Things (IoT) amongst other recent technological innovations. They are used to detect and respond to some form of input or stimulus from the environment we are living in. There are different types of sensors in the market nowadays, depending on the materials used for their manufacture and their applications, namely position sensors, pressure sensors, gas sensors, etc. Gas sensors use semiconductors as materials. Metal oxides, conducting polymers, carbon nanotubes, graphene, and transition metal chalcogenides are some semiconductors materials used in gas sensors. Metal oxides are very good gas sensors materials due to their low cost, high stability, and sensitivity but their high operating temperature disqualify them. Conducting polymers are also good sensors materials due to their flexibility and low operating temperature but they are altered by humidity. To counteract humidity problem, conducting polymers need to be modified or doped with selected elements or molecules. In this project, cellulose was drugged with carbon nanotube (CNT) to create a mechanically and chemically stable structure, which can interact and sense many gases. The chemical and physical properties of cellulose make it a potential material for the development of conductive and potential sensing stuff. This led to the focus of this investigation, which is the development of mixed cellulose nanocrystal (CNC) – CNT materials for sensor application. The CNC was synthesized through the Tempo oxidation method, and various amounts of CNT were added into the CNC below the aggregation threshold of 2.5% using ultrasonication to form a CNC – CNT rectangular sheet. The developed mixed materials were characterized using Scanning Electron Microscopes (SEM) and Transmission Electron Microscope (TEM) to determine the morphology. Fourier Transform Infrared (FTIR), Raman Spectroscopy and X-ray Diffraction (XRD) were employed to investigate the structure of the final material, while TGA has shown similar degradation temperatures of CNC and CNC – CNT. SEM images showed an interconnected network-like structure with a porous architecture assembled by curved thin sheets, and the increase in CNT resulted in aggregate formation within the CNC. TEM micrographs confirmed the structure of CNC, which was rod-like and artefactual dendrites particles, and the presence of CNT in the matrix, while FTIR confirmed the main functional groups of the mixed matrix sheet. The degree of graphitization and presence of disordered cellulose in the mixed materials were determined by Raman spectroscopy to vary between 0.98 and 1.2. The XRD pattern has shown that the crystallinity index of the CNC – CNT composite is correlated to the increase in the concentration of CNT. However, the TGA data has shown that the CNC – CNT materials exhibited similar thermal behaviour, this is expected, since the concentrations of the composites have similar bonding structure and configuration compared to the pristine CNC. It is also evident that the increase in CNT content reduces the thermal degradation (reduced slope) of the CNC. The research work has developed CNC – CNT materials for sensor applications. The composite has exhibited sensor response and thereby detected H2, CO2, NO2 and Ar gases at room temperature through the changes in their electrical conductivities. The ability of CNC-CNT to respond to these gases at room temperature opens-up the possibility for its easy use in indoor and outdoor monitoring.
A dissertation was presented in fulfilment of the requirements for the Master of Science degree, to the Faculty of Sciences, School of Chemistry, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Sensor; Carbon nanotubes; Carbon nanocrystal; UCTD; SDG-9: Industry, innovation and infrastructure